An Overview on Identification and Regulatory Mechanisms of Long Non-coding RNAs in Fungi - Li, Juan; Liu, Xiaoying; Yin, Ziyu; Hu, Zhihong; Zhang, Ke-Qin (Frontiers in Microbiology, 2021)
For decades, more and more long noncoding RNAs (lncRNAs) have been confirmed to play important functions in key biological processes of different organisms. At present, most identified lncRNAs and those with known functional roles are from mammalian systems. However, lncRNAs have also been found in primitive eukaryotic fungi, and they have different functions in fungal development, metabolism, and pathogenicity. In this review, we highlight some recent researches on lncRNAs in the lower eukaryotic fungi, particularly focusing on the identification of lncRNAs and their regulatory roles in diverse biological processes.